1995
DOI: 10.1139/z95-136
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a trade-off between defensive morphology and startle-response performance in the brook stickleback (Culaea inconstans)

Abstract: It is generally believed that predation pressure may drive the evolution of long spines, a robust pelvic girdle, and a deep body in sticklebacks (Pisces: Gasterosteidae). However, the lack of such traits in environments under intense predation pressure suggests that there may be a limit to which these apparently defensive structures benefit sticklebacks. In some environments, well-developed defensive structures may not increase stickleback survival, but may actually reduce fitness if there is a cost associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…Evolutionary trade-offs in antipredator adaptations have been reported in other organismal groups (Losos et al 2002;Blanchard & Moreau 2017). Among fishes, such tradeoffs have been proposed (McLean & Godin 1989;Brainerd & Patek 1998) and supported by evidence at the population-level for a select number of fish species (Andraso & Barron 1995;Bergstrom 2002;Leinonen et al 2011). We believe this is the first study to demonstrate a trade-off in antipredator adaptations on a macroevolutionary scale, among closely related fish species.…”
Section: Solitary Facultative Grazersupporting
confidence: 73%
“…Evolutionary trade-offs in antipredator adaptations have been reported in other organismal groups (Losos et al 2002;Blanchard & Moreau 2017). Among fishes, such tradeoffs have been proposed (McLean & Godin 1989;Brainerd & Patek 1998) and supported by evidence at the population-level for a select number of fish species (Andraso & Barron 1995;Bergstrom 2002;Leinonen et al 2011). We believe this is the first study to demonstrate a trade-off in antipredator adaptations on a macroevolutionary scale, among closely related fish species.…”
Section: Solitary Facultative Grazersupporting
confidence: 73%
“…Reduced encounter rates with vertebrate predators should relax selection for defensive armor in benthics (Reimchen and Nosil 2002). Although we know of no good studies measuring the energetic costs of building armor, Andraso and Barron (1995) demonstrated a trade-off between defensive armor and escape-response performance in brook stickleback (Culaea inconstans), implying that the cost of elaborated armor may be worth paying only in the presence of vertebrate predators. Thus, the combination of release from predation by vertebrates and an increase in mortality by invertebrate predators should favor reduction in defensive armor elements in benthics.…”
Section: Discussionmentioning
confidence: 99%
“…Each species implements a specific response to the threat of predation based on its evolutionary history. Prey species and individuals that possess morphological defenses exhibit fewer behavioral alterations in response to predation risk than species lacking such defenses (Abrahams, 1995;Andraso & Barron, 1995;Hulthén, Chapman, Nilsson, Hollander, & Brönmark, 2014). Because various morphological and behavioral adaptations form a multidimensional defense strategy, in which each species has its own anti-predator niche (Eklöv & Persson, 1995;Whittaker, Levin, & Root, 1973), each species can possibly occupy its local optimum in the landscape of threat (Brown & Vincent, 1992).…”
Section: Discussionmentioning
confidence: 99%